Geração de propriedade intelectual nas empresas da Rede Petrogas de Sergipe - Santos, Maraiza Santana dos (2015)
The principle of generation of intellectual property can be considered a supportive factor for generating new technologies, products and processes and requires the creation of innovative companies, as well as the protection and transfer of technology in various fields of knowledge, especially innovations that are aimed to the market need. Innovation as market activity is the exploration of new ideas to improve business, creating competitive advantages and generating success, being performed by the company, individually or in partnership with other companies or institutions also adapting ideas of other domestic or foreign companies. Thus, the Petroleum Network and Sergipe gas is associated with other networks in the state and in Brazil as well as with international companies in order to integrate with institutions, governments and companies in actions that favor the development of the production chain oil, gas and energy, stimulating the expansion and new ventures openings, in addition to investment in RD & I. The Network also invests in promoting the development of products and services with quality, safety, respect for the environment and social responsibility and the strengthening of companies, through training, certification, protection of innovations, focusing on new markets. The present study reports the results of a research on the generation of intellectual property in Petrogas Network / SE in order to map the intellectual protection in companies with technology-based Network. Methodologically, were conducted literature searches and field research, which was performed in the Network and semistructured interviews with questions to managers and visit the SEBRAE - Brazilian Service of Support for Micro and Small Enterprises - and, finally, data processing and interpretation of results. As a preliminary search result, you can identify what is still a small number of companies Petrogas Network / SE protected innovations and / or who have completed technology transfers, despite all the existing innovation and technology, made partnerships and funding resources, requiring a more active culture among Network companies on the importance of protecting an invention, a device or process.